Conformidade cooperativa e a administração tributária do futuro - Denny, Diogo Cristian (2023)
The traditional model of relationship between the Tax Administration and taxpayers, which place them on opposite sides with a mutual sense of distrust, is worn out and insufficient to achieve the goals that challenge the Tax Administration. It is a consensus in the scientific community that the priority given to a reactive approach no longer ensures the effectiveness of tax revenue collection. The challenges of the current era, which involve, on one hand, high technological power, transnational transactions, digital economy, among other factors, and on the other hand, the need to increase the tax revenue to achieve the constitutional objectives demand a new way of acting based on proactive and compliance-oriented activities. In pursuit of the restoration of public trust in the relationship between taxpayers and Tax Administrations, the concept of "co-operative relationship" was discussed at the Forum on Tax Administration (FAT) and later became the subject of study and recommendation by the Organization for Economic Cooperation and Development – OECD. Throughout this work, the evolution of this theme in Brazil will be studied, as well as its current stage at the federal level. Various initiatives from other countries and some federative units of Brazil will also be examined. Finally, institutes and measures will be proposed to contribute to the compliance program initiative being developed within the Brazilian Tax Administration – RFB, aiming to align it with the OECD recommendations and initiatives of cutting- edge foreign tax administrations. To enhance the work, the hypothetical-deductive method was used, through the qualitative technique, with documental analysis of legal texts, treaties and international conventions, as well as national and international bibliography on the subject.